Study the Effect of Plant Pathogenic Fungi in solid media in comparison with common Fungicide (Baghdad Science Journal, 2013)
A study carried out for study effect of furfural that extracted from corn cobs by using specialized reaction system laboratory on phytopathogenic fungi: Pythium aphanidermatum, Rhizoctonia solani, Macrophomina phaseolina and Fusarium solani in addition to biocontrol fungus Trichoderma viride were isolated from infected plants and from their rhizosphere . The preparation results of different concentrations from stock solution in concentration 1% of furflural showed that The concentration was 100 ppm of furfural was inhibited the growth of P. aphanidermatum46.7 % and the was in concentration 400 ppm. while the concentration 500 ppm caused inhibition 50% and 41.1% of R. solani and F. solani respectively. Whereas the concentration 500 ppm didn’t cause inhibition of M.phaseolina. The concentration 1500 ppm caused the complete inhibition of R. solani and M.phaseolina .Also the concentration 500 ppm of furfural caused46.7 % inhibition of T.viride and complete inhibition in the concentration 1500 ppm .However complete inhibition of F. solani in the concentration 2500 ppm. The concentration 25ppm active ingredient (a. i.) of Ridomil caused 100% inhibition of P. aphanidermatum, while The concentration 20 ppm active ingredient (a. i.)of Benomyl caused 100% inhibition of R. solani and M. phaseolina, and 25ppm active ingredient (a. i.) caused 100% inhibition of F.solani. There was no effect of heat treatment (121C0) on furfural activity against the fungi .